Adverse Effect of Highly Active Anti-Retroviral Therapy (HAART) In HIV/AIDS Patients - Khan, Kashif Ullah; Khan, Amer Hayat; Sulaiman, Syed Azhar; Soo, Chow Ting; Aftab, Raja Ahsan (Indian Journal of Pharmacy Practice)
HIV/AIDS remains the greatest public health concern in the world. With current scenario, HIV-AIDS is considered as a chronic disease due to the advent of highly active antiretroviral therapy that has significantly improved the status of infected population, making HIV a manageable illness. However, recent studies suggest that exposure to antiretroviral medications may have marked adverse effects, independent of HIV status. All antiretroviral drugs can have both short-term and long-term adverse events. The risk of specific side effects varies from drug to drug, from drug class to drug class, and from patient to patient. A better understanding of the adverse effects of antiretroviral agents is of interest not only for HIV specialists as they try to optimize therapy, but also for other physicians who care for HIV positive patients. Current article reviews a note on demerits of the therapy, major complications and metabolic abnormalities that occur as a consequence of highly active anti-retroviral therapy (HAART). Conclusion: It is critical that all health care providers and patients be trained to recognize the symptoms and signs of most of the adverse drug reactions early on. Proper protocols for management of the condition should be readily available. Adverse event surveillance at facilities offering HAART need to be formalized. Proper surveillance of side-effects will enable evidence-based decisions to be taken to avoid potentially fatal complications.
Keywords: Lactic Acidosis; hypersensitivity rash; neuropsychiatric disorders; hepatotoxicity; co-morbid condition